Examination of the Relationship between Psychosocial Mediators and Intervention Effects in It’s Your Game: An Effective HIV/STI/Pregnancy Prevention Intervention for Middle School Students - Elizabeth Baumler; Jill Glassman; Susan Tortolero; Christine Markham; Ross Shegog; Melissa Peskin; Robert Addy; Heather Franks (AIDS Research and Treatment)
A set of mediation analyses were carried out in this study using data from It’s Your Game. . .Keep It Real (IYG), a successful HIV/STI/pregnancy prevention program. The IYG study evaluated a skill and normbased. HIV/STI/pregnancy prevention program that was implemented from 2004 to 2007 among 907 urban low-income middle school youth in Houston, TX, USA. Analyses were carried out to investigate the degree to which a set of proposed psychosocial measures of behavioral knowledge, perceived self-efficacy, behavioral, and normative beliefs, and perceived risky situations, all targeted by the intervention, mediated the intervention’s effectiveness in reducing initiation of sex. The mediation process was assessed by examining the significance and size of the estimated effects from the mediating pathways. The findings from this study provide evidence that the majority of the psychosocial mediators targeted by the IYG intervention are indeed related to the desired behavior and provide evidence that the conceptual theory underlying the targeted psychosocial mediators in the intervention is appropriate. Two of the psychosocial mediators significantly mediated the intervention effect, knowledge of STI signs and symptoms and refusal self-efficacy. This study suggests that the underlying causal mechanisms of action of these interventions are complex and warrant further analyses.